EXPLORING THE HEMODYNAMIC AND POST-OPERATIVE IMPLICATIONS: A COMPARATIVE ANALYSIS OF INTRAVENOUS SEDATION WITH DEXMEDETOMIDINE VERSUS PROPOFOL IN CARDIAC SURGICAL PROCEDURES - LASHARI, AA; AHMED, I; SHAHZAD, MI; TAYYAB, M; OMAIR, M; RANA, MA (Biological and Clinical Sciences Research Journal, 2023)
A comparative study was conducted to examine the impact of dexmedetomidine and propofol on hemodynamic stability and post-operative outcomes in cardiac surgery patients. The study included 100 patients aged 15-60 who were ASA physical Status I-III and scheduled for elective open-heart surgery. Patients were divided into the dexmedetomidine group (n=50) and the propofol group (n=50). The study meticulously detailed hemodynamic assessments, induction protocols, and anesthesia management. The study found that dexmedetomidine exhibited consistently lower heart rates at critical intervals. In the post-operative phase, dexmedetomidine showed favorable outcomes, including significantly shorter ventilation duration (6.43 ± 8.86 vs. 8.86 ± 5.60 hours, P = 0.014) and ICU stay (92.34 ± 56.71 vs. 118.56 ± 41.89 hours, P = 0.01). The incidence of delirium was also significantly lower in the dexmedetomidine group (8% vs. 24%, P = 0.029), suggesting potential neuroprotective effects. It is important to note that the study’s sample size was moderate and focused on short-term outcomes. Therefore, further research is needed to explore diverse patient subgroups and the long-term implications of dexmedetomidine and propofol in cardiac surgery anesthesia. Nonetheless, the study concluded that dexmedetomidine demonstrated favorable hemodynamic stability and beneficial post-operative outcomes, making it a promising option for cardiac surgery patients